Home Switch Control using Electromyograph and AVR Microcontroller - Markis, Lince; Wardana, P. Susetyo; Novi (International Journal of Advanced Science Computing and Engineering, 2023)
The increasingly rapid development of technology in the field of biomedical engineering, one of which is applying EMG (Electromyograph) signals to move mechanical devices.  Various studies have been carried out with various methods tested. The research entitled "Home Switch Control using Electromyograph and AVR Microcontroller" is directed at EMG signals in the arm muscles as input to actuate several switch devices which are usually used in homes or hospitals. The results of placing electrodes at 3 points, namely Bicep Brachii, Tricep Brachii, and Wrist Flexor, produce an EMG signal which has 2 different truth values during contraction after extraction using a moving average and thresholding algorithm, so that the final result produces an on-off control system for 1 switch.